Digital Resources for Managing Wetlands: The Case of Playa Lake Research: A Preliminary Report - Bill Johnson; Marina Oliver (Issues in Science and Technology Librarianship)
Playa lakes are a significant landform found in arid and semiarid climates. They provide water for wildlife, wetlands for waterfowl, flood control for municipalities, and many yield commercial quantities of evaporite minerals. This article discusses digital resources relating to playa lake research.